2018
DOI: 10.1002/brb3.1180
|View full text |Cite
|
Sign up to set email alerts
|

Gene mutations in a Han Chinese Alzheimer's disease cohort

Abstract: ObjectiveAlzheimer's disease (AD) is the most common form of dementia characterized by memory loss at disease onset. The gene mutations in the amyloid precursor protein (APP), presenilin 1 (PSEN1), and presenilin 2 (PSEN2) are the frequent causes of AD. However, the clinical and genetic features of AD overlap with other neurodegenerative diseases. The present study aimed to identify the clinical and genetic characteristics in a Han Chinese AD cohort.MethodsDetailed clinical assessment was applied to all the pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 37 publications
1
12
1
Order By: Relevance
“…The mutation frequency is lower in our cohort than reported in Caucasians; 17 of 129 (13.2%) young‐onset AD patients had PSEN1 mutations in a previous study (Lanoiselee et al, 2017). However, the mutation frequency in our cohort is higher than those conducted in a previous Chinese study with 1 of 108 young‐onset and familial AD patients (0.9%) had PSEN1 mutations (Ma et al, 2019). The variant c.G438A (p.M146I) in PSEN1 is potentially a mutation hot spot, as it contributes to three‐fourths of young‐onset AD patients having a PSEN1 mutation.…”
Section: Discussioncontrasting
confidence: 79%
“…The mutation frequency is lower in our cohort than reported in Caucasians; 17 of 129 (13.2%) young‐onset AD patients had PSEN1 mutations in a previous study (Lanoiselee et al, 2017). However, the mutation frequency in our cohort is higher than those conducted in a previous Chinese study with 1 of 108 young‐onset and familial AD patients (0.9%) had PSEN1 mutations (Ma et al, 2019). The variant c.G438A (p.M146I) in PSEN1 is potentially a mutation hot spot, as it contributes to three‐fourths of young‐onset AD patients having a PSEN1 mutation.…”
Section: Discussioncontrasting
confidence: 79%
“…The patient showed symptoms of cognitive decline and memory impairment, as well as atypical neurological symptoms [64]. The p.H169N mutation of PSEN2 reported by Ma et al has also been detected in both AD and FTD patients, in support of the previous finding by Shi et al [58,63]. A known PSEN2 mutation (p.V139M) which was first reported in an Italian LOAD patient, was observed in a Chinese patient with early-onset disease phenotypes [39,73].…”
Section: Psen2supporting
confidence: 76%
“…Structural analyses indicated that these mutations might induce structural alterations in γ-secretases due to the change in interaction patterns, thereby participating in the pathogenesis of FAD [40]. The p.L226R mutation of PSEN1, which is located at the transmembrane domain of the protein, was reported in an EOAD family characterized by language impairment at disease onset [58]. In a whole-exome sequencing study on 15 Chinese FAD patients, Jiang et al identified six previously reported PSEN1 mutations in all subjects, including p.M139I, p.T147I, p.L173W, p.F177S, p.R269H, and p.R157S [39].…”
Section: Psen1mentioning
confidence: 99%
See 2 more Smart Citations